Pengaruh Return On Asset (ROA) Dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Manufaktur yang Terdaftar di Indonesia Periode 2017-2019 - Mahdi Hendrich (Institut Rahmaniyah Sekayu, 2020)
This study attempts to examine how much influence these two variables, namely ROA and ROE, on stock prices, especially in manufacturing companies of the type of